Effect of solvent type and concentration on size and morphology of arbidol microparticles obtained by supercritical antisolvent precipitation - Vorobei, A. M. (Russian Journal of Physical Chemistry B, 2017)
The capability of arbidol microparticle preparation by supercritical antisolvent (SAS) precipitation was demonstrated. A nonmonotonic dependence of the average particle size on the concentration was found, while the position of the minimum is dependent on the type of solvent used. It is possible to prepare Arbidol particles of various morphology and size from several microns to several hundred microns depending on the conditions.